Does Subculture Matter? A Cross-Cultural Study of Chronism and Attitudes toward Download Delay in Internet Systems in China and the United States. Issue 2 (3rd April 2019) - Rose, Gregory; Wu, Wilfred; Yu, Yanjun
ABSTRACT: The majority of interface delay research and practitioner literature recommends minimizing delay as much as possible. However, a very limited number of studies have identified cultural chronism which may make the desirability of trading functionality and resources for minimal delays inappropriate within certain populations. Specifically, members of monochronic cultures highly value speed in system response, while those of polychronic cultures do not. This current study extends existing literature to investigate a previously unexplored culture and subculture, respectively, Han Chinese and African Americans, and their attitudes toward download delay and trading download delay for better functionality.